Comparing self-reported leisure-time physical activity, subjective health, and life satisfaction among youth soccer players and adolescents in a reference sample - Wold, B.; Duda, J.; Balaguer, I.; Smith, O.; Ommundsen, Y.; Hall, H.; Samdal, O.; Heuzé, J.; Haug, E.; Bracey, S.; Castillo, I.; Ramis, Y.; et al. (2013)
The aim of the study was to examine to what extent young people who play organised soccer rate their leisure-time moderate-to-vigorous physical activity, life satisfaction, and health more positively and higher than a same-aged population-based reference group (including some adolescents who also played organised soccer). Data from two samples of five countries (England, France, Greece, Norway, and Spain) were included: a sample of soccer players aged 10-14 years who participated in the Promoting Adolescent Physical Activity project [Duda, J.L., Quested, E., Haug, E., Samdal, O., Wold, B., Balaguer, I.,... Cruz, J. (2013). Promoting Adolescent health through an intervention aimed at improving the quality of their participation in Physical Activity ('PAPA'): background to the project and main trial protocol. International Journal of Sport and Exercise Psychology] and a nationally representative reference sample of 11- and 13-year olds from the Health Behaviour in School-aged Children study. Results from multivariate logistic regression analysis showed that the participants in the soccer sample, in particular girls, reported a higher level of moderate-to-vigorous leisure-time physical activity than those in the reference sample. They also rated their life satisfaction and subjective health more favourably than the reference sample. The associations did not differ according to age or socio-economic status. The results suggest that playing soccer is a positive activity for youth and seems to be a very potent way of increasing regular moderate-to-vigorous physical activity among girls. Thus, efforts aimed at increasing participation in organised youth soccer may potentially be beneficial to young people's psychosocial health and hold the potential to increase physical activity, particularly among girls. © 2013 International Society of Sport Psychology.